A Novel Energy-Efficient Routing with Adaptive Receiver Using Cross-Layer Design in Wireless Sensor Networks - Abinaya, R; Bhuvaneshwari, C; Gayathri, R (International Journal of Engineering and Technology, 2018)
The increasing demand of wireless sensors in mission critical applications renders the Quality-of-Service (QoS) to be one of vital issue in wireless sensor network. It is necessary to deal with the underlying variance between energy efficiency and QoS, since sensor networks have different resource constraints. To manage these constraints such as unreliable links, limited power and other environmental factors in sensor networks, cross-layer approach is designed to ensure QoS. Recent routing protocols rely on the duty-cycle which causes sensor nodes to lose ample amount of energy by monitoring idle channels. In addition, opportunistic forwarding of packet leads to multiple receiverâ€™s receiving the same packet which induces redundancy. To address these issues, we propose a novel Opportunistic Routing with Adaptive REceiver (O-RARE) protocol as an alternative to duty cycle mechanism. The proposed work aims at reducing idle listening and redundancy by enabling low-power receiver at physical layer. Hence O-RARE is designed to ensure reliable and adaptive routing in our work through interactions among cross-layer. Â Â